The impacts of renewable energy, financial inclusivity, globalization, economic growth, and urbanization on carbon productivity: Evidence from net moderation and mediation effects of energy efficiency gains. (August 2022) - Murshed, Muntasir; Apergis, Nicholas; Alam, Md Shabbir; Khan, Uzma; Mahmud, Sakib
Abstract: Although the relevance of establishing low-carbon economic growth has been extensively highlighted in the Paris Agreement and the Sustainable Development Goals declarations, the analysis of the macroeconomic determinants of carbon productivity has remained overlooked in the literature. Therefore, this study makes a novel attempt to evaluate whether energy efficiency gains, along with renewable energy use, financial inclusivity, economic growth, globalization, and urbanization, improve carbon productivity in the emerging seven countries between 2007 and 2018. Moreover, the study contributes to the literature by predicting the net moderating and mediating effects of energy efficiency improvements on carbon productivity. The findings support that enhancing the level of energy use efficiency by 1% helps to improve carbon productivity by around 0.3% in the long run. In addition, the predicted net effects reveal that energy efficiency gains exert a moderating effect on the level of carbon productivity and reverse the negative impact of financial inclusivity, trade globalization, and urbanization on carbon productivity. However, energy efficiency gains cannot moderate to neutralize the carbon productivity-inhibiting impact associated with economic growth. Moreover, the analysis shows that energy efficiency gains mediate to jointly boost carbon productivity alongside higher renewable energy use. Lastly, financial globalization is evidenced to enhance carbon productivity in the emerging seven countries in the long run. Accordingly, a set of relevant policies are recommended. Highlights: 1% improvement in energy efficiency enhances carbon productivity by 0.3%. Energy efficiency improvement exerts moderating and mediating effects. Renewable energy use does not directly influence carbon productivity. Financial inclusivity, economic growth, and urbanization reduce carbon productivity. Globalization exerts heterogeneous impacts on carbon productivity.